THE EFFECT OF SATISFACTION, BRAND TRUST, BRAND IMAGE ON REPURCHASE INTENTION WITH BRAND COMMITMENT AS A MEDIATION - Rahellia Panjaitan; Yomeini Margareth; Ayu Dwi Hasty (CV. Radja Publika, 2025)
The purpose of this researchis to analyzethe effect of Satisfaction, Brand Trust, Brand Image on Repurchase Intention with Brand Commitment as Mediation. The data are obtained directly from the distribution of questionnaires with google docs and whatsapp to consumers who have bought products in Ikea. The sample of respondents in this study was 220 employees. The results of the questionnaire where processed usingstructural equation model (SEM) with the help of AMOS 23.0. software. Hypothesis testing results show that Satisfaction has no effect on Brand Commitment, Brand Trust has a significant effect on Brand Commitment, Brand Image has a significant effect on Brand Commitment, Brand Commitment has a significant effect on Repurchase Intention, Satisfaction has no significant effect on Repurchase Intention with Brand Commitment as mediation, Brand Trust has a significant effect on Repurchase Intention Intention with Brand Commitment as mediation, Brand Image has a significant effect on Repurchase Intention with Brand Commitment as mediation